A Game Theory-Based Vehicle Cloud Resource Allocation Mechanism - Prado Marques, Henrique Andrews; Meneguette, Rodolfo I. (Revista Eletrônica de Iniciação Científica em Computação, 2022)
The vehicle cloud aims at efficient cooperation in communication, task allocation, and sharing of resources in VANETs since computational resources embedded in the vehicle can be used to offer resources for the provision of cloud services. This requires efficient resource management mechanisms that allocate these resources to maximize their use. Thus, in this paper, we propose a resource allocation mechanism based on Game Theory to maximize the use of resources made available by vehicles. The results obtained showed greater use of the resources made available by the vehicles compared to other works in the literature.